PENGARUH DISIPLIN KERJA REWARD DAN PUNISHMENT TERHADAP KINERJA BERDASARKAN PERSEPSI KARYAWAN HOTEL MAXONE BALIKPAPAN - Nainggolan, Hermin; Anhar, Bani; Wulandari, Devi (Jurnal GeoEkonomi, 2024)
Competition in business development in Indonesia is one of the phenomena that a company needs to pay attention to, with globalization in the economic sector today which is increasingly opening up opportunities for foreign entrepreneurs to participate in competence in attracting consumers. This research aims to investigate the influence of work discipline, reward, and punishment on performance based on the perceptions of employees at Hotel Maxone Balikpapan, both partially and simultaneously. The research data were obtained from the performance reports of employees over a 5-year period from 2018 to 2022, with a sample size of 58 respondents. The data analysis technique employed was assisted by the SPSS 27 program. Based on the hypothesis testing results, partially, it was found that the independent variable (work discipline) has a positive and significant effect on employee performance, with a calculated t-value of 2.701 > than the t-table of 1.674, and a significance value of 0.009 < the (α) value of 0.05. The independent variable (reward), partially, also has a positive and significant effect on employee performance, with a calculated t-value of 3.521 > than the t-table of 1.674, and a significance value of 0.001 < the (α) value of 0.05. However, the independent variable (punishment), partially, has a negative and significant effect on employee performance, with a calculated t-value of -2.311 < than the t-table of 1.674, and a significance value of 0.025 < the (α) value of 0.05. Simultaneously, the results indicate that work discipline, reward, and punishment significantly influence employee performance, with a calculated F-value of 25.603 > than the F-table of 2.78, and a significance value of 0.000 < the (α) value of 0.05.